Differences in Prices and Price Risk across Alternative Marketing Arrangements Used in the Fed Cattle Industry - Muth, Mary K.; Liu, Yanyan; Koontz, Stephen R.; Lawrence, John D. (2012)
Information on prices and price risk differences across marketing arrangements aids fed cattle producers in making choices about marketing methods. As part of the congressionally mandated Livestock and Meat Marketing Study, we investigated fed cattle price and price risk differences across marketing arrangements. The analysis uses data representing cattle purchased by 29 large beef packing plants from October 2002 through March 2005. Results indicate that marketing agreements offered the best tradeoff between price level and price risk. Forward contracts had the lowest average yet highly volatile prices. Auction barn prices were higher than other methods but also the most volatile.